(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This article is aimed to review the applications of Polyether Ether Ketone (PEEK) in dentistry. The evolving desire for functions and aesthetics, few drawbacks with existing materials and clinicians shifting their paradigms towards metal free restorations led space for the metal-free restorations in today’s restorative practice. PEEK is a polymer based innovative material, that can be used in either fixed or removable prosthetics. This literature review discusses various applications and uses of PEEK.